1992
DOI: 10.1002/jso.2930510215
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma in a child with oculocutaneous albinism

Abstract: Malignant melanoma is extremely rare in patients with albinism. To date, in the English language literature, there have been only sixteen documented cases of malignant melanoma in albino patients. These cases include thirteen cutaneous, one oral, one ocular, and one anal; only one of these was in a child. Here, we present the case of the youngest known albino patient to have cutaneous malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…This seems to indicate that melanin protects better against nonmelanomas than against CMM or, alternatively, that melanin may be a photocarcinogen for CMM, in agreement with our hypothesis. Furthermore, albinism is associated with nonmelanoma skin cancer but not to the same extent with CMM (21)(22)(23). Albino Africans have a substantially larger risk of getting skin cancer than normally pigmented Africans (24).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to indicate that melanin protects better against nonmelanomas than against CMM or, alternatively, that melanin may be a photocarcinogen for CMM, in agreement with our hypothesis. Furthermore, albinism is associated with nonmelanoma skin cancer but not to the same extent with CMM (21)(22)(23). Albino Africans have a substantially larger risk of getting skin cancer than normally pigmented Africans (24).…”
Section: Discussionmentioning
confidence: 99%
“…Albinism is an autosomal recessive disorder of melanin synthesis that affect the skin, eyes and hair. Melanocytes are normally distributed in the eye and skin, but normal amounts of melanin are not synthesised 12. The most frequently encountered tumour is squamous cell carcinoma, with basal cell carcinoma seen less often 12 13.…”
Section: Discussionmentioning
confidence: 99%
“…Melanocytes are normally distributed in the eye and skin, but normal amounts of melanin are not synthesised 12. The most frequently encountered tumour is squamous cell carcinoma, with basal cell carcinoma seen less often 12 13. Malignant melanoma is very rare in oculocutaneous albinism,12 14 but this low incidence is unexplained 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that in these animals there is tyrosinase expression in the cells; this likely contributed to the synthesis of melanin by the tumor. In humans, approximately 77% of patients with albinism had amelanotic lesions (LEVINE et al, 1992).…”
Section: Case Reportmentioning
confidence: 99%